Peranan Pengetahuan dalam Proses Bisnis Internasional - Murhadi, Werner R. (Jurnal Widya Manajemen & Akuntansi, 2003)
Internationalization occurs when a firm expands its selling, production or other business activities into international market. Managers strategically use information to achieve degree of internationalization. Information reflected by internal and external social capital influences the acquisition and creation of knowledge, and that knowledge is a key resource driving the international business growth. Knowledge seen as an intangible factor has main influence on international business process.